Learning English based on Education Environment - Ahdar Yos; Rafiqa Rafiqa; Yosef Teguh Siregar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The focus of the problem statement of this article is whether the educational environment can develop English vocabulary? This study aims to find out that the education environment can develop students’ vocabulary. The significance of this study is expected to give useful information on English teaching and learning process, especially in learning English vocabulary based on the education environment. In this case, the researcher used experimental as a research method, and She used random sampling technique in choosing the sample. Vocabulary test as a research instrument, it consists of 20 items, then pretest and posttest were used to collected data, statistic analysis as a technique of data analysis. Based on the result of the data analysis and the discussion of the result in the previous chapter, the writer would like to put forward conclusion that the school environment is a good medium in the teaching-learning process especially to develop students’ vocabulary